2019
DOI: 10.3390/ijerph17010257
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption Frequency of Parents and Stress Status of Their Children: Korea National Health and Nutrition Examination Survey (2007–2016)

Abstract: Background: The effect of stress on mental health has been increasingly acknowledged. Drinking habits are closely inter-related with stress and each affects the other. However, only limited studies addressed the effects of alcohol consumption on family members apart from spouses. The purpose of this study is to better understand the relationship between parent drinking frequency and their children’s self-reported stress. Methods: Data was collected from the Korean National Health and Nutrition Examination Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
1
2
0
2
Order By: Relevance
“…Results from linear and binary logistic regressions showed that having heavy-drinking parents, compared with having moderate-drinking parents, was associated with an increased likelihood of reporting psychological and somatic complaints and perceived stress, even when adjusting for sociodemographic characteristics. These findings reflect earlier studies that have found associations between problematic parental drinking and adverse health among offspring in the general population [ 11 15 ] and among adolescents of parents with alcohol use disorder [ 5 7 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results from linear and binary logistic regressions showed that having heavy-drinking parents, compared with having moderate-drinking parents, was associated with an increased likelihood of reporting psychological and somatic complaints and perceived stress, even when adjusting for sociodemographic characteristics. These findings reflect earlier studies that have found associations between problematic parental drinking and adverse health among offspring in the general population [ 11 15 ] and among adolescents of parents with alcohol use disorder [ 5 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…Information collected only from the adolescents themselves, in conjunction with a focus on problematic drinking, rather than overall consumption, are methodological features that might underestimate the total harms that parental drinking entails since adolescents are not likely to have full knowledge about their parents' alcohol habits and the parent-child relationship could influence the perception of their parents' drinking. One exception is a study done on Korean data, which found that parent-reported frequency of drinking was associated with adolescent self-perception of stress [15]. Nonetheless, calls for more studies on alcohol's harm to others using data collected from the drinker and the victim separately have been made [3].…”
Section: Introductionmentioning
confidence: 99%
“…En este estudio, los adolescentes reportaron que es al papá a quien perciben en mayor frecuencia con problemas de consumo de alcohol, seguido de un consumo de ambos padres, y un consumo solo de la mamá. Estos hallazgos concuerdan con otros estudios en México (Mondragón et al, 2022) y en el mundo (Bendtsen et al, 2013;Homel y Warren, 2019;Kim et al, 2020;Li et al, 2017), en donde se reportan problemas asociados con el consumo de ambos padres. Todo ello destaca la importancia de estudiar estos problemas y su asociación con conductas disruptivas en los hijos, así como detallar los posibles efectos negativos de esta asociación a largo plazo.…”
Section: Discusión Y Conclusionesunclassified
“…En tanto, Homel y Warren (2019) encontraron que en el caso del papá con consumo problemático, son las hijas quienes presentan mayor consumo. Aunado a esto, el papá es el progenitor que reporta un mayor consumo de alcohol (Bendtsen et al, 2013;Homel y Warren, 2019;Kim et al, 2020;Li et al, 2017;Mondragón et al, 2022). Finalmente, si ambos padres presentan problemas relacionados con el consumo, los hijos presentan afectaciones por igual, sin importar el sexo.…”
Section: Introductionunclassified
“…In the United States (U.S.), 12.3% of children aged 17 or younger (8.7 million children) live with at least one parent with a SUD [ 1 ], and it is unknown how many children live with other household members with a SUD. These children are more likely to develop a SUD themselves [ 2 , 3 , 4 , 5 , 6 ], and to live in traumatic environments [ 3 ], experience social difficulties [ 1 , 7 , 8 ], parental abuse [ 1 , 9 , 10 , 11 , 12 ], and stress [ 13 , 14 ]. Children with at least one parent with a SUD are also more likely to develop mental health and/or behavioral disorders [ 9 , 15 , 16 , 17 , 18 , 19 ], and some studies suggest that these associations vary by the children’s age [ 20 ] and sex [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%